2014
DOI: 10.4103/2231-0762.144586
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of canine retraction by in vivo method using four brands of elastomeric power chain

Abstract: Objective:To investigate the amount of space closure by movement of canines into the extraction spaces using four brands of elastomeric power chains (EPCs) by intraoral application with pre-adjusted appliance for 6 weeks.Materials and Methods:The sample size calculation was based on the studies of Boester and Johnston and also with repeated measures analysis of variance (ANOVA) continuous data for force degradation, standard deviation of 24.9 g, and also from a pilot study, which totaled to around 17 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 21 publications
1
15
0
5
Order By: Relevance
“…Kanuru et al (19) (2014) investigated the amount of space closure by movement of canines into the extraction spaces using four brands of elastomeric chains for 6 weeks. They said that although all brands of the elastomeric chains produced space closure of canines, it was observed that not much of a significant difference existed among the products tested.…”
Section: The Effect Of Different Types Of Elastomeric Chains and Diffmentioning
confidence: 99%
“…Kanuru et al (19) (2014) investigated the amount of space closure by movement of canines into the extraction spaces using four brands of elastomeric chains for 6 weeks. They said that although all brands of the elastomeric chains produced space closure of canines, it was observed that not much of a significant difference existed among the products tested.…”
Section: The Effect Of Different Types Of Elastomeric Chains and Diffmentioning
confidence: 99%
“…Their advantages are no patient cooperation required, low cost, smooth surface, and their irritation-free nature. 10,11 The objectives of this research were to evaluate the effectiveness of piezocision-assisted canine distalization using three-dimensional (3D) measurements and to assess the transversal changes, postdistalization gingival status, and mobility scores.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, a recently introduced flexible material was included-the power chain, made of rubber, used in orthodontics for traction and which may be an interesting alternative for splinting (26). It has also been used in traumatology in the treatment of fractures of the jaws (34).…”
Section: Discussionmentioning
confidence: 99%
“…The splint must hold the tooth in place and allow it to move slightly and not be too stiff for optimal healing. Recently, more flexible materials have been introduced in orthodontics , and some of these may even be suitable for splinting of teeth. Moreover, the splint must be easy to make, be affordable for the patient and dentist, and be esthetically pleasing.…”
Section: Aimsmentioning
confidence: 99%
See 1 more Smart Citation